Effects of Tamoxifen on DNA Integrity in Mice - Sadeghi, Sepideh; Talebi, Alireza; Shahedi, Abbas; Moein, Mohammad Reza; Abbasi-sarcheshmeh, Abolghasem (Journal of Reproduction & Infertility, 2019)
Background: Tamoxifen (TX) is widely used to treat idiopathic infertility in men. Using TX has been shown to produce sperm in patients with oligospermia and azoospermia and improve male fertility. The aim of this study was to evaluate the effects of TX on DNA and chromatin quality in mice regarding the importance of chromatin quality and sperm DNA at all stages of reproduction. Methods: 24 male NMRI mice were divided into 3 groups including dose 0.4 mg/kg/day that received basal diet and TX, dose 0.6 mg/kg/day that received basal diet and TX, and group 3 that received vehicle for 35 days as the control. After that, epididymal spermatozoa were analyzed for nuclear DNA quality. One-way ANOVA was performed with a Tukey test to compare sperm DNA fragmentation at different times. The p<0.05 was considered significant. Results: The use of different doses of TX may have detrimental effects on sperm chromatin protamination and DNA integrity in mice. According to Acridine Orange (AO) staining, the rate of increased single-stranded DNA damage was observed at 0/6 mg/kg/day TX dose (p<0.05). Conclusion: The use of different studied TX doses in the animal sample was found to increase the amount of protamine deficiency and DNA defect in treated mice.